The Relationship Between Environmental Sanitation and Nutritional Status with Soil- Transmitted Helminths Infection in Elementary School Children - Asnita Yani; Balqis Nurmauli Damanik (International Journal of Health and Social Behavior, 2024)
Poor environmental sanitation and malnutrition are the leading causes of STH infection. This study aims to determine the relationship between ecological sanitation, nutritional status, and STH infection incidence in elementary school children. This type of research is descriptive research. The research location is UPT SDN 060831, Medan City. The sample was 32 respondent, Medan City students, obtained using the total sampling technique. Data was collected using questionnaire instruments, Body Mass Index (BMI) examinations, and fecal examinations. The data were further analyzed univariately. The results showed that most environmental sanitation conditions did not qualify, such as latrine conditions (68.8%), SPAL conditions (75.0%), trash can conditions (87.5%), and clean water facilities (68.8%). Nutritional status (BMI/U) was most in the normal category (65.6%), and no helminth eggs were found in respondents (negative STH), so a relationship analysis could not be carried out. It is suggested that the school and parents support government programs related to providing mass worm- prevention drugs.